Eureka Lake, Riley County - Woodson, Alexander (Kansas State University, The Chapman Center for Rural Studies, 2017)
This paper examines the history of Eureka Lake, a short lived resort southwest of Manhattan, Kansas.
Alexander Woodson, “Eureka Lake, Riley County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/201.
Keywords: beach; oxbow lake; Riley County; resort; Mary Wood; Eureka Lake